Electrostatic field effects on membrane domain segregation and on lateral diffusion - Wilke, Natalia (2011)
Natural membranes are organized structures ofneutral and charged molecules bearing dipole momentswhich generate local non-homogeneous electric fields.When subjected to such fields, the molecules experiencenet forces that can modify the lipid and protein organization,thus modulating cell activities and influencing (oreven dominating) the biological functions. The energeticsof electrostatic interactions in membranes is a long-rangeeffect which can vary over distance within r−1 to r−3. In thecase of a dipole interacting with a plane of dipoles, e.g. aprotein interacting with a lipid domain, the interaction isstronger than two punctual dipoles and depends on the sizeof the domain. In this article, we review several contributionson how electrostatic interactions in the membraneplane can modulate the phase behavior, surface topographyand mechanical properties in monolayers and bilayers.